A Comprehensive Analysis of the Relationship Between GDP and the Global Hunger Index Over the Last 20 Years - Reuveni, Saada (Technium Social Sciences Journal, 2024)
This study examines the relationship between Gross Domestic Product (GDP) per capita and the Global Hunger Index (GHI) over the past two decades. By analyzing data from various countries across different income levels, the research explores how economic growth intersects with hunger dynamics. The study utilizes reputable sources, including reports from the Food and Agriculture Organization (FAO), the International Food Policy Research Institute (IFPRI), and the World Bank. The findings highlight that while GDP per capita is an important factor in reducing hunger, other elements such as income inequality, education, health expenditure, agricultural productivity, and governance significantly influence hunger outcomes. The research underscores the necessity for holistic approaches that integrate economic growth with social equity and effective policy interventions to eradicate hunger globally.